Genome-wide identification and expression profiling of the U-box gene family in poplar under salt stress - Dong, Zhi; Li, Jun; Gong, Yinchen; Li, Shaoran; Wu, Tiandong; An, Yibo; Luo, Lian (Frontiers in Plant Science, 2026)
IntroductionThe U-box gene family, defined by the presence of a conserved U-box domain, participates in various biological processes, particularly in plant responses to abiotic stress. However, a comprehensive analysis of this gene family in Populus trichocarpa has not yet been conducted. Investigating the characteristics of U-box genes in poplar will deepen our understanding of the molecular mechanisms underlying salt tolerance and provide a theoretical basis for enhancing its environmental adaptability.MethodsIn this study, we performed a genome-wide identification and characteristic analysis of the U-box gene family. Analyses included phylogenetic relationships, gene structures, conserved motifs, promoter cis-acting elements, chromosomal distribution, gene duplication events, and synteny with other plant species. In addition, the expression patterns of selected U-box genes under salt stress were validated using quantitative real-time PCR (qRT-PCR).ResultsIn this study, 103 U-box genes were identified in the P. trichocarpa genome and mapped to 18 chromosomes. These genes encode proteins with molecular weights ranging from 9.5 to 129.3 kDa and isoelectric points between 4.31 and 9.08, with most predicted to localize in the nucleus. Promoter analysis revealed numerous cis-acting elements associated with development, abiotic stress responses, growth regulation, and hormone signaling. Collinearity analysis identified 4 tandem and 30 segmental duplication events. Transcriptome data showed that 40 and 21 PtrPUBs were differentially expressed in roots and leaves, respectively, under salt stress.DiscussionThese findings suggest that U-box genes may play important roles in regulating poplar’s salt stress response. Overall, this study provides a theoretical foundation and valuable genetic resources for the identification of salt tolerance genes in poplar.